The socioeconomic position of national minorities with a special emphasis on Slovenes in Croatia over the past thirty years - Riman, Barbara (Razprave in gradivo - Inštitut za narodnostna vprašanja (1990), 2023)
The article presents the situation of members of the Slovene community in Croatia, focusing on selected aspects of their socioeconomic participation (inclusion) in Croatian society. This topic has not been thoroughly studied yet, firstly due to the low interest of researchers in the position and activities of members of the Slovene community in Croatia, and secondly due to a continuous lack of data on the socioeconomic participation of members of not only the Slovene community but of all minorities in Croatia in general. Based on the analysis of data mainly collected from Croatian official reports, the situation of members of the Slovene minority in Croatia is presented mainly in relation to the exercise of their rights to education and employment.
Keywords: education of national minority; izobraževanje narodne manjšine; labour market; narodne manjšine na Hrvaškem; national minorities in Croatia; Slovene minority in Croatia; slovenska manjšina na Hrvaškem; socialnoekonomska vključenost narodne manjšine; socioeconomic participation of national minority; trg dela